Mitochondria as a Therapeutic Target: Focusing on Traumatic Brain Injury - Randhall Bruce Carteri (Journal of Integrative Neuroscience)
Mitochondria are organelles of eukaryotic cells delimited by two membranes and cristae that consume oxygen to produce adenosine triphosphate (ATP), and are involved in the synthesis of vital metabolites, calcium homeostasis, and cell death mechanisms. Strikingly, normal mitochondria function as an integration center between multiple conditions that determine neural cell homeostasis, whereas lesions that lead to mitochondrial dysfunction can desynchronize cellular functions, thus contributing to the pathophysiology of traumatic brain injury (TBI). In addition, TBI leads to impaired coupling of the mitochondrial electron transport system with oxidative phosphorylation that provides most of the energy needed to maintain vital functions, ionic homeostasis, and membrane potentials. Furthermore, mitochondrial metabolism produces signaling molecules such as reactive oxygen species (ROS), regulating calcium levels and controlling the expression profile of intrinsic pro-apoptotic effectors influenced by TBI. Hence, the set of these functions is widely referred to as ‘mitochondrial function’, although the complexity of the relationship between such components limits such a definition. In this review, we present mitochondria as a therapeutic target, focus on TBI, and discuss aspects of mitochondrial structure and function.